The ginsenoside metabolite compound K stimulates glucagon-like peptide-1 secretion in NCI-H716 cells by regulating the RhoA/ROCKs/YAP signaling pathway and cytoskeleton formation - Fengyuan Tian; Xi Wang; Haixiang Ni; Xiaohong Feng; Xiao Yuan; Qi Huang (Elsevier, 2021)
Ginsenoside Rb1 has been shown to have antidiabetic and anti-inflammatory effects. Its major metabolite, compound K (CK), can stimulate the secretion of glucagon-like peptide-1 (GLP1), a gastrointestinal hormone that plays a vital role in regulating glucose metabolism. However, the mechanism underlying the regulation of GLP1 secretion by compound K has not been fully explored. This study was designed to investigate whether CK ameliorates incretin impairment by regulating the RhoA/ROCKs/YAP signaling pathway and cytoskeleton formation in NCI-H716 cells. Using NCI-H716 cells as a model cell line for GLP1 secretion, we analyzed the effect of CK on the expression of RhoA/ROCK/YAP pathway components. Our results suggest that the effect of CK on GLP1 secretion depends on the anti-inflammatory effect of CK. We also demonstrated that CK can affect the RhoA/ROCK/YAP pathway, which is downstream of transforming growth factor β1 (TGFβ1), by maintaining the capacity of intestinal differentiation. In addition, this effect was mediated by regulating F/G-actin dynamics. These results provide not only the mechanistic insight for the effect of CK on intestinal L cells but also the molecular basis for the further development of CK as a potential therapeutic agent to treat type 2 diabetes mellitus (T2D).